Determining the lifetime of the first 4+ state in 182Pt - Stolze, Sanna (2011)
In this work the mean lifetime of the First 4+ state in 182Pt was determined by using the Recoil Distance Doppler-Shift method. The studied nuclei were produced in the 86Kr(100Mo, 4n)182Pt fusion-evaporation reaction. The RDDS method exploits the fact that the observed γ-ray energy depends on the velocity of the emitting nucleus. Using a degrader foil after the target enables measuring the intensities of γ-rays emitted before and after the degrader. The recoil-gated γγ spectra were analyzed separately for each target-to-degrader distance and the lifetime was determined with the Differential Decay Curve Method, which takes into account the lifetimes of the feeding states. The lifetime of the 4+ state in 182Pt was determined to be τ = 40:8(14) ps. This corresponds to a transition quadrupole moment of |Qt| = 6:90(12) eb. When comparing the quadrupole moment to other N = 104 isotones it is clear, even when taking into account the charge dependence of the quadrupole moment, that the quadrupole moment of the prolate 4+ state in 186Pb is significantly larger. Also the quadrupole moments decrease with decreasing Z. Before drawing any final conclusions about the collectivity of the prolate band in 182Pt it is neccessary to determine the lifetimes of other yrast excited states at low energies.